1975
DOI: 10.1148/115.1.47
|View full text |Cite
|
Sign up to set email alerts
|

The Wandering Gallbladder

Abstract: An unusual case of a hypermobile gallbladder and liver is presented. The liver and gallbladder, supported only by a long midline falciform ligament, rotated freely from the right to the left upper quadrant. Because of a long gastrohepatic ligament and mesocolon, intermittent volvulus of the stomach and colon were associated findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

1976
1976
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…An exceedingly rare third variant consists of a normally fixed gallbladder to a mobile liver lobe free of its coronary and triangular ligaments. 9 In addition, to these mechanisms, as shown in our case, twisting of fundus along the axis of gallbladder body is another mechanism of gallbladder torsion.…”
Section: Discussionsupporting
confidence: 54%
“…An exceedingly rare third variant consists of a normally fixed gallbladder to a mobile liver lobe free of its coronary and triangular ligaments. 9 In addition, to these mechanisms, as shown in our case, twisting of fundus along the axis of gallbladder body is another mechanism of gallbladder torsion.…”
Section: Discussionsupporting
confidence: 54%
“…Chiavarini et al in 1974 described a case of a 22-year-old with daily episodes of abdominal pain since childhood with a transient hyperbilirubinemia. 2 Likewise, Laso et al reported an 81-year-old female with abdominal pain and a palpable mass in the epigastrium and right upper quadrant. 9 Preoperative diagnosis is difficult and rarely made.…”
Section: Discussionmentioning
confidence: 97%
“…1 Its characteristic propensity for torsion places it at risk for necrosis. 2 It is believed to be present in 4% to 5% of the population and is associated with other anatomic abnormalities such as a hypermobile liver 4 or an unusually long or absent mesentery. 1 Fewer than 10 cases of wandering gallbladder have been reported in the literature.…”
mentioning
confidence: 99%
“…It is thought that there must be an underlying defect of gallbladder attachment, most commonly the gall bladder hanging from the liver on a congenital mesentery of variable length, connecting to the gallbladder and cystic duct along their length, or connecting to the cystic duct alone, leaving a freely moving gallbladder [3]. Very rarely, a hypermobile gallbladder is due to a hypermobile liver secondary to absence of coronary and triangular ligaments [4]. Another reported anatomical variation that may be an underlying defect is an aberrantly proximal origin of the cystic duct from the right hepatic duct, constituting a very narrow cystic pedicle [5].…”
Section: Discussionmentioning
confidence: 99%